Geraubte Identität Die gewaltsame "Eindeutschung" von polnischen Kindern in der NS-Zeit - Hopfer, Ines (2010)
Stolen identity - the forced "Germanization" of "racially valuable" children during National Socialism, illustrated by the country of Poland. Heinrich Himmler, acting in his capacity as "Reich Commissioner for the Strengthening of German Foldom", ordered the selection of "racially valuable" polish children for "Germanization" - the Teutonic blood had to be collected even if it meant kidnapping children. For this reason polish children from orphanages, schools, forster parents, parents who refused to sign the "Volksliste" and parents who had been murdered or sent to forced labor or concentration camps had to have a "racial" examination - children who possessed the Nordic features were regarded as suitable for the "Germanization" and were distributed in special children homes. At these special children homes the children were forced to give up their own identity step by step: the children got new German names and had to learn German, moreover contact with relatives at home was painfully forbidden. In Austria, known as "Ostmark" during National Socialism, two special places were found, where polish children were confronted with "Germanization practices": the children home "Alpenland" in Oberweis next to Gmunden and the resettlement camp "Parsch" in Salzburg. After a "successful Germanization" the children were placed in German and Austrian forster families. There the children were treated in different ways: some children became a part of the family, they felt safety and comfortable and were treated like their own children. Other polish girls and boys were treated badly: the forster families took advantage of their defencelessness, they abused and beat the polish children, they reagard them just as cheap labourer. After the war only a small number of such kidnapped children was tracked by the several tracking services like UNRRA, IRO or the Polish Red Cross. But further problems arose when German and Austrian forster families or the children themselves opposed the repatriation to Poland. Being back in Poland, the polish children were regarded as children of the enemy - regarded as "German" of the polish society.